A review of key strategies to address the shortage of analgesics and sedatives in pediatric intensive care - Castro, Roberta Esteves Vieira de; Rodríguez-Rubio, Miguel; Magalhães-Barbosa, Maria Clara de; Prata-Barbosa, Arnaldo; Holbrook, Jaimee; Kamat, Pradip; Stormorken, Anne (Frontiers in Pediatrics, 2022)
Importance: Targeted analgosedation is a challenge in critically ill children, and this challenge becomes even more significant with drug shortages. Observations: Published guidelines inform the provision of analgosedation in critically ill children. This review provides insights into general approaches using these guidelines during drug shortages in Pediatric Intensive Care Units as well as strategies to optimize both pharmacological and non-pharmacological approaches in these situations. Conclusions and Relevance: Considering that drug shortages are a recurrent worldwide problem, this review may guide managing these drugs in critically ill children in situations of scarcity, such as in pandemics or disasters.